Find solutions of the given equation in the form of power series $$y'' +2xy' = 0$$

My approach:

$$2xy' = 2a_1x + 2\times2a_2x^2 + 2\times3a_3x^3 + ... = \sum 2ia_{i}x^{i}$$ $$y'' = 2a_2 + 3\times2a_3x + 4\times3a_4x^2 + ... = \sum (i+1)(i+2)a_{i+2}x^{i}$$

So to have $y'' +2xy' = 0$ we need to have every coefficient equal to $0$.


$x^0$ // $2a_2 + 0 = 0 => a_2=0$

$x^1$ // $3\times2a_3 + 2a_1 = 0 => a_3 = -a_1/3$

$x^2$ // $4\times3a_4 + 2\times2a_2=0 => a_4 = -4a_2/12 = 0$


So it was easy to observe that every even coefficient is equal to $0$ and every odd one can be written in terms of $a_0$

Afterwards I wanted to find a recursive formula for odd coefficients and this is a problem that I can't solve.

I tried doing it in that way: $$2n(2n+1)a_{2n+1} + 2(2n-1)a_{2n-1} = 0$$ $$a_{2n+1} = -\frac{2(2n-1)a_{2n-1}}{2n(2n+1)}$$

Now probably it should be somehow easy to write it as a recursive formula in terms of $a_0$, but I can't really see it.


You already did most of the job.

We continue \begin{align*} \color{blue}{a_{2n+1}}&= -\frac{2(2n-1)}{(2n+1)2n}a_{2n-1}\\ &=+\frac{2(2n-1)2(2n-3)}{(2n+1)2n(2n-1)(2n-2)}a_{2n-3}\\ &=\cdots\\ &=(-1)^n\frac{2^n(2n-1)!!}{(2n+1)!}a_1\tag{1}\\ &=(-1)^n\frac{2^n}{(2n+1)(2n)!!}a_1\tag{2}\\ &\,\,\color{blue}{=\frac{(-1)^n}{(2n+1)n!}a_1}\tag{3} \end{align*}


  • In (1) we use the double factorial $(2n-1)!!=(2n-1)(2n-3)\cdots3\cdot 1$.

  • In (2) we use $(2n)!=(2n)!!(2n-1)!!$ and $(2n)!!=(2n)(2n-2)\cdots 4\cdot2$.

  • In (3) we use $(2n)!!= 2^n n!$.

Since we already know that $a_{2n}=0, n\geq 0$, we get from (3) the generating function $A(x)$ \begin{align*} A(x)=\sum_{n=0}^\infty a_nx^n=\sum_{n=0}^\infty a_{2n+1} x^{2n+1}=a_1\sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)n!} x^{2n+1} \end{align*} and the general solution \begin{align*} A(x)+C\color{blue}{=a_1\sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)n!} x^{2n+1}+C}\qquad\qquad a_1,C\in\mathbb{R} \end{align*}

Note that $A(x)=\frac{a_1\sqrt{\pi}}{2}\mathrm{erf}(x)$ where $\mathrm{erf}$ is the error-function.


Let the solution of the given ODE be $y=\sum c_{s}x^{s}$. Then this satisfies the equation $y^{''}+2xy^{'}=0$. Now, $y^{'}=\sum sc_{s}x^{s-1}$ and $y^{''}=\sum s(s-1)c_{s}x^{s-2}$. Substituting these values in the differential equation.

$\sum s(s-1)c_{s}x^{s-2} + 2x \sum sc_{s}x^{s-1}=0$
$=>\sum s(s-1)c_{s}x^{s-2} + 2\sum sc_{s}x^{s}=0$
$=>\sum 0(0-1)c_{0}x^{0} + \sum 1(1-1) c_{1}x^{1} + \sum_{s=2} s(s-1)c_{s}x^{s} + 2\sum 0c_{0}x^{0} + 2\sum_{s=1} sc_{s}x^{s}=0$
$=>\sum_{s=0} (s+1)(s+2)c_{s+2}x^{s} + 2\sum_{s=0} (s+1)c_{s+1}x^{s+1} =0$

Now since the last relation is an identity, therefore

$(s+1)(s+2)c_{s+2}=0$ and $2(s+1)c_{s+1}=0$

Now I think you can see the recurrence relation


Assume $y = \displaystyle \sum_{j = 0}^{\infty} a_j x^{s+j}$ with $a_0 \ne 0$.

We find $$\sum_{j = 0}^{\infty} a_j (s+j)(s+j-1)x^{s+j-2} + 2 \sum_{j = 0}^{\infty} a_j(s+j) x^{s+j} = 0$$

Substituting for lowest power of $x$ at $j=0$, $$a_0 s (s-1) = 0 \implies s= 0$$ For $j=1$, $$a_1 .s(s+1)+2a_1.(s+1) = 0 \implies a_1 = 0$$

For recurrence relation collect the coefficients of $x^{s+j}$, $$a_{j+2}(s+j+2)(s+j+1) + 2a_{j}(s+j)=0$$ $$a_{j+2} = \frac{-2a_{j}(s+j)}{(s+j+2)(s+j+1)}$$

Since $a_1 = 0$, all the odd coefficients are zero. You will obtain two solutions; one for $s = 0$, other for $s = 1$. Can you proceed from here?

  • $\begingroup$ I am not really used to the notation with these "s" and "j" letters, so it will take me a while to analyze. Thanks. $\endgroup$ – James Smith Jan 27 at 13:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.